A novel multi-dimensional modeling approach to integrated municipal solid waste management - Asefi, Hossein; Lim, Samsung (Journal of cleaner production, 2017)
An integrated system for waste reduction, collection, composting, recycling, and disposal is required to tackle the growing challenge of municipal solid waste management. Integrated Solid Waste Management (ISWM) involves many executive, operational and managerial decisions such as the siting of waste processing and disposal units, selection of waste-treatment technologies and allocation of waste flow to processing facilities and landfills. This study aims to satisfy the sustainability requirements for designing an ISWM system by taking economic, environmental and social factors into account. The present study utilized Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) in the Geographic Information System (GIS) environment and developed a reliable Suitability Indicator for siting the ISWM system's components. A new model is developed to minimize the fixed cost, minimize the transportation cost and maximize the suitability of the entire system. Considering the real-world constraints, the proposed model is proven to be practical, efficient and case-independent for designing an ISWM system and supporting the existing systems in both developing and developed countries. To realize the model effectively, the augmented version of ε-constraint is employed so that the model is implemented in the General Algebraic Modeling System (GAMS) software. The proposed approach is successfully applied to the existing ISWM system of Tehran, Iran, and the results show that 12%, 22% and 17% improvement can be achieved in terms of the fixed cost, transportation cost and total suitability of the system, respectively. •A new multi-dimensional modeling approach is proposed to optimize the ISWM system.•Multiple economic, environmental and social objectives and criteria are considered.•A solid indicator is developed to assess the suitability of the ISWM system.•GIS, Delphi, TOPSIS and ε-constraint methods are integrated to solve the model.